Treatment of class I malocclusion with severe crowding with asymmetrical extractions - Lavado Torres, Ana (2020)
The present report describe the case of an 11-year-old female patient, treated at the Dental Center at School of Dentistry at the University San Martin de Porres, who underwent a treatment of class I malocclusion with severe crowding with asymmetric extractions. This case was selected by several factors including the complexity of the mechanics used, the type of malocclusion, anchorage managment and collaboration by the patient. The apparatus used and the protocol used are described. Finally, the results obtained at the end of the treatment are shown